2012
DOI: 10.3109/0886022x.2011.646808
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Mortality in Stable Peritoneal Dialysis Patients

Abstract: Background: The mortality rates of end-stage renal disease patients have significantly declined over the past decade. However, there are few reports on the risk factors for mortality in stable peritoneal dialysis (PD) patients who survive for a considerable time. Patients and methods: We reviewed the medical records and identified all adult patients who received PD between April 2001 and March 2009 in our institution. The total cohort was 550 patients. Among these patients, 383 patients were enrolled as stable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
13
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 25 publications
2
13
1
Order By: Relevance
“…In our study neither of the drugs caused a change of serum CRP, which is a common but unspecific inflammatory marker in the dialysis patients including those treated with peritoneal dialysis [34]. Similar observations on the lack of an effect of aliskiren on CRP were made by Andersen et al [18].…”
Section: Discussionsupporting
confidence: 73%
“…In our study neither of the drugs caused a change of serum CRP, which is a common but unspecific inflammatory marker in the dialysis patients including those treated with peritoneal dialysis [34]. Similar observations on the lack of an effect of aliskiren on CRP were made by Andersen et al [18].…”
Section: Discussionsupporting
confidence: 73%
“…Serum albumin level is an important predictor of all-cause mortality in both PD and hemodialysis patients [37], [38]. As frequently there is a reciprocal interaction between serum albumin and CRP levels, some studies have shown that on multivariate Cox regression analysis, serum CRP level instead of serum albumin level remains significant in predicting mortality [39]. In contrast, our study showed that both serum HS-CRP and albumin levels were independent risk factors for mortality and technique failure.…”
Section: Discussioncontrasting
confidence: 70%
“…In line with our results, a study from USA found RRF was an important predictor of 1-year mortality in chronic PD patients by analyzing a national database—the End-Stage Renal Disease Core Indicators Project20. Another study from Korea demonstrated low RRF was significantly correlated with mortality of those who maintained PD for more than 2 years21. The plausible explanations for the importance of RRF in predicting mortality include reducing volume overload, reducing use of hypertonic dialysis solutions, increasing renal clearance of larger molecular weight molecules2223.…”
Section: Discussionmentioning
confidence: 99%